A Case of Hereditary Pancreatitis Presenting as Recurrent Abdominal Pain in a 11 Year Old Girl - Das, A; Basu, M (Journal of Nepal Paediatric Society, 2015)
Recurrent abdominal pain is a common problem among children. Since its first description by John Apley in 1958, the condition has remained poorly understood with a multitude of factors being implicated in causation. The symptoms tend to be vague and investigations seldom show organic disease. But the importance to evaluate each child with recurrent abdominal pain should be considered important nevertheless, particularly, in protracted cases. Here, we present a case who presented with history of recurrent abdominal pain for several years before being diagnosed as a case of hereditary pancreatitis. This stresses the importance of evaluating each case with a detailed and complete history, physical examination and selected investigations. J Nepal Paediatr Soc 2015;35(1):57-58